(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1974)
Ground pelleted citrus pulp replaced 15% of corn on rations fed to pigs from 22 to 95 kg. Experiment followed a randomized complete block design with two treatments and five replicates. Average daily gains and feed/gain were: A (0% citrus pulp) — .901 kg and 3.16, B (15% citrus pulp) — .863 kg and 3.06. No statistical significant differences were noticed. Equally no significant effect was detected for carcass length (cm ) : A = 77.3 and B = 78.8; leg lenght (cm ): A = 57.0 and B = 58.1; backfat thickness (cm ): A - 3.93 and B = 3.69; loin eye area (cm2) : A = 24.73 and B = 23.32; dressing (% ) : A — 78.5 and B = 77.1; lean cuts (% ) : A — 4 4 .7 and B = 47.1; separable fat (% ) : A - 37.2 and B = 35.2.